2020
DOI: 10.21203/rs.3.rs-117893/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Excessive Intake of Longan Arillus Alters Gut Homeostasis and Aggravates Colitis in Mice

Abstract: BackgroundLongan is the fruit of Dimocarpus longan Lour. and the longan arillus has been used in traditional Chinese medicine for thousands of years possessing various health benefits. However, the excessive intake of longan is found in daily life to cause “shanghuo” syndrome. Shanghuo has been linked to increased disease susceptibility. The present study thus aimed to investigate the toxicological outcomes after excess longan treatment.MethodsLongan extract at a normal dosage of 4 g/kg and two excess dosages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
(38 reference statements)
2
4
0
Order By: Relevance
“…20 norank_f__Muribaculaceae was also decreased in high fructose fed mice and colitis mice. 36,37 In the present study, HFCD also significantly decreased the proportion of norank_f__Muribaculaceae, and this trend was reversed by oryzanol. Oscillospiraceae was a conditional pathogenic gut bacteria and reported to be associated with inflammation, 38 its overgrowth induces intestinal inflammation.…”
Section: Food and Function Papersupporting
confidence: 59%
“…20 norank_f__Muribaculaceae was also decreased in high fructose fed mice and colitis mice. 36,37 In the present study, HFCD also significantly decreased the proportion of norank_f__Muribaculaceae, and this trend was reversed by oryzanol. Oscillospiraceae was a conditional pathogenic gut bacteria and reported to be associated with inflammation, 38 its overgrowth induces intestinal inflammation.…”
Section: Food and Function Papersupporting
confidence: 59%
“…Consistent with our results, high doses of Nigella sativa seed polysaccharides have been shown to significantly increase the abundance of Muribaculaceae_unclassified in streptozotocin-treated mice. 33 Huang et al 34 found that excessive longan intake aggravated alterations of dextran sulfate sodium–associated bacteria, including higher abundance of Proteobacteria at the phylum level and Bacteroides , Akkermansia , Turicibacter , and the Escherichia – Shigella group at the genus level, as well as lower levels of Muribaculaceae. Taken together, our data revealed that the gut microbiota composition in DOX-treated rats was in a state of microbial dysbiosis, and treatment could neutralize this disorder, specifically by altering the abundance of Proteobacteria and Bacteroidetes .…”
Section: Discussionmentioning
confidence: 99%
“…After the herbal intervention, we found that SJZD improved the composition of intestinal fora and increased the relative abundance of genera dominated by norank_f__Muribaculacea, Bacteroides, norank_f__Lachnospiraceae, and Parabacteroides. Norank_f__Muribaculaceae and Lachnospiraceae_UCG-001 exerted positive efects on immune regulation, stimulated immune development and defense, and showed antiinfammatory efects [59][60][61]. Bacteroides have the capacity for immunomodulation, and their encoded bd oxidase renders their colonization of the intestine and positive alterations of the intestinal environment easier [54].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they can mediate the diferentiation of immune cells, such as T1, T2, and T17 to decrease airway infammation in patients with asthma [71]. In these patients, TLR2 is expressed at high levels [61], particularly in the large and small airways [72]. TLR2 can recognize many types of bacterial cell wall components.…”
Section: Discussionmentioning
confidence: 99%